2016
DOI: 10.1038/cr.2016.4
|View full text |Cite
|
Sign up to set email alerts
|

SIRT6 safeguards human mesenchymal stem cells from oxidative stress by coactivating NRF2

Abstract: SIRT6 belongs to the mammalian homologs of Sir2 histone NAD+-dependent deacylase family. In rodents, SIRT6 deficiency leads to aging-associated degeneration of mesodermal tissues. It remains unknown whether human SIRT6 has a direct role in maintaining the homeostasis of mesodermal tissues. To this end, we generated SIRT6 knockout human mesenchymal stem cells (hMSCs) by targeted gene editing. SIRT6-deficient hMSCs exhibited accelerated functional decay, a feature distinct from typical premature cellular senesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
255
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 268 publications
(277 citation statements)
references
References 59 publications
(96 reference statements)
8
255
2
1
Order By: Relevance
“…Interestingly, these cells showed premature and progressively accelerated cellular senescence as demonstrated by several senescent markers and also exhibited elevation of reactive oxygen species (ROS), dysregulated redox metabolism, and increased sensitivity to oxidative stress. Contrary to a prior work performed in mouse embryonic fibroblasts (MEFs) [7], SIRT6 −/− hMSCs did not exhibit enhanced genomic instability [9], suggesting that cell type differences may underlie the divergent phenotypes. Indeed, Pan et al [9] found that transcriptional changes upon SIRT6 depletion in hMSCs were not recapitulated in human vascular endothelial cells.…”
contrasting
confidence: 52%
See 2 more Smart Citations
“…Interestingly, these cells showed premature and progressively accelerated cellular senescence as demonstrated by several senescent markers and also exhibited elevation of reactive oxygen species (ROS), dysregulated redox metabolism, and increased sensitivity to oxidative stress. Contrary to a prior work performed in mouse embryonic fibroblasts (MEFs) [7], SIRT6 −/− hMSCs did not exhibit enhanced genomic instability [9], suggesting that cell type differences may underlie the divergent phenotypes. Indeed, Pan et al [9] found that transcriptional changes upon SIRT6 depletion in hMSCs were not recapitulated in human vascular endothelial cells.…”
contrasting
confidence: 52%
“…Until now, however, SIRT6 has not been associated with oxidative stress. A new study from Pan et al [9] links the deacetylase activity of SIRT6 to redox homeostasis in human mesenchymal stem cells (hMSCs) and suggests that this activity may regulate the longevity and progeria phenotypes ( Figure 1). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Knocking down GPX7 in wild‐type HMSCs resulted in accelerated cellular aging (Figure 5f–h). To investigate whether the metformin‐Nrf2‐GPx7 pathway could protect HMSCs in an in vivo context, HMSCs were implanted into the tibialis anterior muscle of immune‐deficient mice, and their in vivo retention was measured by an in vivo imaging system (IVIS) (Kubben et al., 2016; Pan et al., 2016; Wang et al., 2018; Yang et al., 2017). Metformin‐treated HMSCs displayed delayed cellular attrition compared to vehicle‐treated cells (Figure 5i), whereas GPX7 ‐deficient HMSCs exhibited accelerated cell exhaustion in the in vivo microenvironment (Figure 5j).…”
Section: Resultsmentioning
confidence: 99%
“…A total volume of 100 μl PBS of 1 × 10 6 HMSCs labeled with luciferase were injected into the midportion of the tibialis anterior muscle of immune‐deficient BALB/c nude mice (Pan et al., 2016); 5 or 6 days after implantation, mice were anesthetized and treated with D‐luciferin. Then, photon emission was measured by the IVIS Lumina System (PerkinElmer).…”
Section: Methodsmentioning
confidence: 99%